Meningkatkan kesiapan karier dan pemahaman peluang kerja di bidang Geomatika pada siswa SMKN 3 Selong - Apriyeni, Baiq Ahda Razula; Supriadi, Herman; Hidayat, Muh. Adrian Juniarta; Hidayat, M. Adnan; Liana, Liana (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
In the era of geospatial technology advancement, understanding geomatics is crucial to prepare students for the increasingly complex job market. This study aims to evaluate the extent to which SMKN 3 Selong students comprehend the geomatics major, career opportunities, and business prospects through geospatial information system mastery. Career guidance approaches were implemented through initial diagnostics, career information dissemination, and evaluation stages. The findings reveal that 92% of students demonstrate a strong interest in Geographic Information Systems (GIS) courses, while 77% feel the need for additional guidance to prepare for careers. Additionally, 54% of students are ready to enter the workforce, although most chose the geomatics major based on external factors. This program is expected to enhance students' understanding of geomatics careers and improve their competitiveness in the job market. This research contributes to developing relevant career guidance strategies for vocational majors